Peran Ganda Guru Dalam Pembelajaran Sastra Pada Kurikulum Merdeka - Namlul Wadi; Muflihaini Muflihaini; Rabbiyatul Saniah; Nur’ainun Ritonga; Aulia Rahman (Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research focuses on the dual role of teachers in learning literature in the independent curriculum. The type of research used is qualitative descriptive research with a literature study approach. The object of the research is the policy of literature in the curriculum on the grounds that literature in the curriculum requires the role of teachers in the application process. The data were obtained through indirect observation techniques, and from other sources such as journals related to literary policies in the curriculum. Data analysis uses literature analysis through the stages of identification, evaluation and interpretation. The results of the study show that the independent curriculum incorporates literature into school lesson hours in the form of co-curricular in learning. Then the dual role of teachers in literary learning includes epistemological roles and axiological roles.